Computer-Aided Efficient Routing and Reliable Protocol Optimization for Autonomous Vehicle Communication Networks - Alaa Kamal Yousif Dafhalla; Mohamed Elshaikh Elobaid; Amira Elsir Tayfour Ahmed; Ameni Filali; Nada Mohamed Osman SidAhmed; Tahani A. Attia; Badria Abaker Ibrahim Mohajir; Jawaher Suliman Altamimi; Tijjani Adam (Computers)
The rise of autonomous vehicles necessitates advanced communication networks for effective data exchange. The routing protocols Ad hoc On-Demand Distance Vector (AODV) and Greedy Perimeter Stateless Routing (GPSR) are vital in mobile networks (MANETs) and vehicular ad hoc networks (VANETs). However, their performance is affected by changing network conditions. This study examines key routing parameters—MaxJitter, Hello/Beacon Interval, and route validity time—and their impact on AODV and GPSR performance in urban and highway scenarios. The simulation results reveal that increasing MaxJitter enhances AODV throughput by 12% in cities but decreases it by 8% on highways, while GPSR throughput declines by 15% in cities and 10% on highways. Longer Hello intervals improve AODV performance by 10% in urban settings but reduce it by 6% on highways. Extending route validity time increases GPSR’s Packet Delivery Ratio (PDR) by 10% in cities, underscoring the need to optimize routing parameters for enhanced VANET performance.